STUDI KERETAKAN GEDUNG DAN AKSES JALAN KAMPUS POLITEKNIK PEKERJAAN UMUM DI KOTA SEMARANG - UTOMO, ADITYO BUDI; Agung Bhakti Utama; Laely Fitria Hidayatiningrum; Andi Patiroi (Politeknik Negeri Semarang, 2025)
The MBH Campus, Public Works Polytechnic (PUtech) located in Semarang City began construction in 2021 - 2022 and functional in early 2023. Six months after its first operation, much damage was found to the building and access roads where there were many cracks in the walls with the same pattern and widening and collapsing in several parts of the garden and access roads that widened over time. A study was conducted to identify the cause of the damage that occurred. The study began by identifying the level of damage to the PUtech campus building and making assumptions regarding the cause of the damage. A more detailed investigation was carried out to strengthen the possibility of suspicions. The analysis was carried out based on the results of field measurements, non-destructive material tests, and soil characteristic tests on the building. The study's results showed a tendency for the building to subside to the north by 0-4 cm per year. The subsidence did not indicate conditions that were dangerous to the building structure because it occurred evenly. The base soil is in the form of cohesive inorganic clay with moderate plasticity so there is a high potential for soil expansion. The soft base soil, classified as soft soil, has the potential for consolidation up to 40 cm due to the existing building load.